Seafood Perceptions among People Aged 55 and Above: Summary of Focus Groups Results - Allen F. Wysocki; Lisa House; William A. Messina (EDIS)
FE821, a 5-page fact sheet by Allen F. Wysocki, Lisa House, and William A. Messina, Jr., provides a brief summary of the focus group part of a study of perceptions of Florida residents aged 55 and over on seafood consumption. Published by the UF Department of Food and Resource Economics, November 2009. Reviewed March 2013.